Problem Based Learning Model Assisted by Nearpod and Its Effect on Learning Outcomes of Environmental Changes - Agustina, Nabila; Kodri Madang; Masagus Mhd. Tibrani (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2025)
The learning process in today's era expects students to be active in the learning proces, In addition, a common problem encountered is the minimal cognitive learning outcomes in biology. Contributing factors include limited learning facilities, teachers' inability to deliver material systematically, and a lack of effective communication, which leads to a decline in students' cognitive engagement. This study aims to determine the effect of the Problem Based Learning model assisted by Nearpod on learning outcomes related to environmental change material. The research method is Quasi-Experimental, with a Non-equivalent Control Group design involving two classes. Data analysis was performed using ANCOVA. The results of the study indicate that the Problem Based Learning model supported by Nearpod has a significant effect on the learning achievement of Environmental Changes (Sig. 0.042 < 0.05). The results of this study indicate that there is an effect of the Nearpod-assisted Problem Based Learning model on the subject of environmental change.